Creative writing: Rhyme scheme used by students in writing poetry - Mustika Pelangi; Yelfiza Yelfiza; Rika Afriyanti (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2025)
This study investigates the use of rhyme schemes in students’ poetry writing, focusing on a case study of Phase F, Grade XI students at SMAN 1 Padang. Using a qualitative analysis of student poetry assignments, the research identifies several types of rhyme schemes employed by students, including couplets, alternate rhymes, enclosed rhymes, terza rima, limericks, and free verse. The findings reveal that many students favored couplet and alternate rhyme patterns due to their clear structure and ease of use, while others used free verse to express ideas more intuitively and flexibly. The study highlights that students’ understanding of rhyme schemes goes beyond formal constraints, serving as a foundation for creativity in poetry writing. It emphasizes the importance of teaching rhyme schemes not merely as rigid structures but as expressive tools in literature and language education. Keywords: Creative Writing; Poetry; Rhyme Scheme